PENGARUH PEMBELAJARAN ABAWANI TERHADAP PRESTASI MATA PELAJARAN BAHASA ARAB PADA SISWA KELAS VII G SEKOLAH MENENGAH PERTAMA TAHFIDZUL QUR’AN ABI UMMI BOYOLALI TAHUN AJARAN 2024/2025 - Astri Susilowati; Sukari Sukari (STKIP Pesisir Selatan, 2025)
Arabic holds a central role in Islamic education as the primary medium for understanding the Qur’an and Hadith. However, in practice many students encounter difficulties in learning Arabic, resulting in relatively low achievement. One innovation applied at SMP Tahfidzul Qur’an Abi-Ummi Boyolali is the use of Abawani learning, a model based on the Kitab Abawani that emphasizes tajwid, articulation of letters, and the basic structure of Arabic. This study aims to analyze the influence of Abawani learning on the Arabic achievement of seventh-grade students in the 2024/2025 academic year. This research employed a quantitative descriptive approach with a total sampling technique involving 30 students. Abawani learning data were collected using a 20-item questionnaire, while Arabic achievement was measured from students’ semester report cards. The data were analyzed through descriptive statistics, validity and reliability tests, normality and linearity tests, and Pearson’s product-moment correlation. The results showed that Abawani learning was at a moderate category with an average score of 60, while students’ Arabic achievement was also at a moderate category with an average score of 50. Hypothesis testing yielded an r-value of 0.016, smaller than the r-table value of 0.361, indicating no significant influence of Abawani learning on Arabic achievement.